Integral representation of a solution of the Cauchy problem for a degenerating hyperbolic equation with retarded argument - Zarubin, A. N.; Зарубин, А. Н.; Зарубин, А. Н. (Institute of Mathematics, NAS of Ukraine, 1997)
By using the method of integral equations, we prove the existence and uniqueness of a regular solution of the Cauchy problem for a degenerating hyperbolic equation with retarded argument.